Immunophenotyping of progenitor cells from articular cartilage of New Zealand Rabbits (Oryctolagus cuniculus). (April 2022) - Hayashi, Rafael Gonçalves; Borghesi, Jéssica; Mario, Lara Carolina; Rabelo, Ana Carolina Silveira; de Almeida da Anunciação, Adriana Raquel; Lima, Mariana Ferreira; Miglino, Maria Angélica; de Oliveira Favaron, Phelipe; Carreira, Ana Claudia Oliveira
Highlights: New Zealand rabbit articular cartilage progenitor cells (ACPC) were obtained. ACPC showed labeling for CD105, but not for CD34. ACPC were able to differentiate into osteogenic, adipogenic, and chondrogenic cells. After application of ACPC in nude mice, no tumor growth was observed. ACPC showed characteristics of mesenchymal stem cell. Abstract: Mesenchymal stem cell (MSC) have immunomodulatory and anti-inflammatory effects, allowing its application in the therapy of different diseases, including articular cartilage injuries, which induce the establishment of a pro-regenerative microenvironment in the injured tissue. Therefore, our objective was to isolate, characterize and differentiate cartilage cells from different joints of New Zealand rabbit ( Oryctolagus cuniculus ), in order to verify their potential as MSC for future clinical use. For this, cartilage fragments were isolated from the humerus-radio-ulnar joints, humeral scapula, femoro-tibio-patellar, and lame femoris from rabbits. The results showed that the cells were rounded in the center of the plate and fibroblastoids in the periphery. After thawing, the cells did not change their growth time in culture, nor their morphology. The cells showed labeling for mesenchymal stem cell, cytoskeleton, pluripotency and cell proliferation, but not for hematopoiesis markers (CD105+ and CD34-). We also observed that, when induced, they were able to differentiate into osteogenic, adipogenic, and chondrogenic cells. After application of these cells in nude mice, no tumor growth was observed in spleen, kidney, liver, lung and heart. Therefore, we conclude that cells isolated from the articular cartilage of rabbits present characteristics of MSC with potential for future clinical applications.